2012
DOI: 10.1002/ece3.302
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and outbreeding depression in Stylidium hispidum: implications for mixing seed sources for ecological restoration

Abstract: The benefits of composite rather than local seed provenances for ecological restoration have recently been argued, largely on the basis of maximizing evolutionary potential. However, these arguments have downplayed the potentially negative consequences of outbreeding depression once mixed provenances interbreed. In this study, we compared intraspecific F1 hybrid performance and molecular marker differentiation among four populations of Stylidium hispidum, a species endemic to Southwestern Australia. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…For example, despite differences in magnitude between quantitative traits and measures of genetic differentiation, Merilä and Crnokrak (2001) found the measures were positively correlated, suggesting that divergence in neutral markers may be indicative of the degree of genetic differentiation in quantitative traits. Likewise, Hufford et al (2012) were able to use molecular marker data to predict the scale of outbreeding depression while other studies have found measures of genetic diversity, like level of inbreeding and number of alleles, were consistent predictors of heterosis when mixing individuals from different populations (Pickup et al, 2013). Studies like these have led to the creation of plant restoration guidelines for the translocation of individuals that rely primarily on levels of genetic diversity and differentiation (e.g.…”
Section: Risk Of Inbreeding and Outbreeding Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, despite differences in magnitude between quantitative traits and measures of genetic differentiation, Merilä and Crnokrak (2001) found the measures were positively correlated, suggesting that divergence in neutral markers may be indicative of the degree of genetic differentiation in quantitative traits. Likewise, Hufford et al (2012) were able to use molecular marker data to predict the scale of outbreeding depression while other studies have found measures of genetic diversity, like level of inbreeding and number of alleles, were consistent predictors of heterosis when mixing individuals from different populations (Pickup et al, 2013). Studies like these have led to the creation of plant restoration guidelines for the translocation of individuals that rely primarily on levels of genetic diversity and differentiation (e.g.…”
Section: Risk Of Inbreeding and Outbreeding Depressionmentioning
confidence: 99%
“…Managing the risks of using local or disparate sources of restoration stock, therefore, needs to account for the genetic context of natural source populations. In general, it appears that mixing slightly differentiated, inbred populations can lead to increased fitness whereas mixing extremely differentiated, locally adapted populations can result in outbreeding depression (Forrest et al, 2011;Hereford, 2009;Hufford et al, 2012;Pickup et al, 2013;Waser, 1993). For example, recent studies by Forrest et al (2011) and Hufford et al (2012) found that plants crossed at intermediate-distances outperform within-population crosses in terms of germination success and survival while long-distance hybrids show signs of outbreeding depression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, if mating between individuals from distant populations disrupts co-adapted gene complexes or introduces maladaptive alleles to locally adapted populations, then their offspring can have lower fitness relative to the offspring of crosses between geographically proximate populations (i.e., outbreeding depression; Waser andWilliams 2001, Edmands 2007). Although the genetic mechanisms that can lead to heterosis and outbreeding depression are wellunderstood (Lynch and Walsh 1998), it has been difficult to predict the fitness effects of crosses between populations (Edmands and Timmerman 2003), and crossing studies have found evidence for both heterosis (e.g., Pickup et al 2013) and outbreeding depression (e.g., Hufford et al 2012).…”
mentioning
confidence: 99%